Zróżnicowanie polskiej leksyki sportowej (między specjalistyczną terminologią a słownictwem potocznym i środowiskowym) - Nowowiejski, Bogusław (Poznańskie Spotkania Językoznawcze, 2014)
The article provides information on the contemporary Polish sports terminology. It provides evidence for its dynamic quantitative development conditioned by various factors, mainly the extra-linguistic ones. Additionally, it points out fundamental qualitative changes, first of all ever progressing stylistic differentiation which finds reflection, among others, in the monographic and lexicographic descriptions of sports vocabulary.